The Effect of Team Characteristics, Organizational Justice, and Work Ethic on Teacher Job Performance - Mansur Hakim (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
The objective of the study was to examine the effect of team characteristics, organizational fairness, and work ethic on the performance of teachers of elementary school in East Jakarta. The research method is quantitative with the survey. The sample of the study was 209 teachers drawn with simple random technics. Data analysis uses descriptive statistics and path analysis. The results conclude: there is a positive direct effect of team characteristics, organizational fairness, and work ethic on teacher performance; there is a positive direct effect of team characteristics and organizational fairness on teacher work ethics; And there is a direct influence of team characteristics directly positive effect on organizational justice. In conclusion, team characteristics, organizational justice, and work ethics have a direct and positive impact on the performance of teachers of Elementary School in East Jakarta. There are suggestions that team characteristics, organizational fairness, and work ethics need to be improved in an effort to improve teacher performance